Kazimierza Sośnickiego pedagogika polityczna. Zapomniany dyskurs - Kwieciński, Zbigniew (Studia Edukacyjne, 2022)
The understanding of political pedagogy by Kazimierz Sośnicki as a kind of comparative pedagogy studies on the relationship between political systems and the educational system, as well as the goals, contents and effects of school actions. Main issues of these studies and their results. A special lecture on fascist and Nazi pedagogy at the secret University in Lviv. Other forms of practicing political pedagogy in interwar Poland. The processes of reproduction of authoritarian systems in the research of M. S. Archer. Linguistic confusion in our public sphere. Hopes for continuations. I intend to contribute to the memento of an important trend in Polish pedagogy, abandoned after the war. In my opinion, it should be included in pedagogy and education. It is necessary both in pedagogy and pedagogical practice to educate for critical political wisdom. In the face of the disarray of political structures and the language of public debates, it is necessary to develop the capacity for an independent position, over partial divisions and fighting. The subject of political pedagogy was practiced with a gusto in the 1930s.